2013
DOI: 10.1089/aid.2012.0197
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: HIV Type 1 Subtype C Variants Transmitted Through the Bottleneck of Breastfeeding Are Sensitive to New Generation Broadly Neutralizing Antibodies Directed Against Quaternary and CD4-Binding Site Epitopes

Abstract: Mother-to-child transmission of HIV-1 subtype C can occur in utero, intrapartum, or via breast milk exposure. While not well understood, there are putative differences in the mechanisms involved with the distinct routes of vertical HIV transmission. Here, we address the question of whether specific viral characteristics are common to variants transmitted through breastfeeding that may facilitate evasion of innate or adaptive immune responses. We amplified the envelope gene (env) from the plasma of six infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Higher SIV dose substantially increases the number of founder variants in macaque studies (93, 139141), and a similar phenomenon has been observed in infants whose mothers seroconvert during breastfeeding (138, 142), likely due to high breast milk viral loads during acute infection. Also, similar to other routes of infection, only CCR5-tropic HIV viral variants establish infection in vivo (137, 142). Consistent with this observation, only macrophages infected with CCR5-tropic virus can migrate through infant oral mucosa to gain access to the HIV target cells of the lamina propria (108).…”
Section: Establishment Of Hiv Infectionmentioning
confidence: 94%
“…Higher SIV dose substantially increases the number of founder variants in macaque studies (93, 139141), and a similar phenomenon has been observed in infants whose mothers seroconvert during breastfeeding (138, 142), likely due to high breast milk viral loads during acute infection. Also, similar to other routes of infection, only CCR5-tropic HIV viral variants establish infection in vivo (137, 142). Consistent with this observation, only macrophages infected with CCR5-tropic virus can migrate through infant oral mucosa to gain access to the HIV target cells of the lamina propria (108).…”
Section: Establishment Of Hiv Infectionmentioning
confidence: 94%
“…The humoral response to HIV-1 infection is marked by the dynamic appearance and disappearance of certain antibody isotypes and subclasses to different viral antigens from acute to longstanding infection. To harness this information for an HIV-1 incidence assay, we tested different antibody forms (i.e., IgM, IgG, IgG3, IgG4, IgA) in concert with a wide variety of HIV-1 antigens (i.e., peptides and proteins derived from env, gag, pol genes) to comprehensively cover the epitopes and antigen structures most likely to be reactive with immune sera from recent to chronic infection, including transmitted/ founder envelope (T/F) proteins (22)(23)(24)(25)(26). The analysis includes the presence or absence of the response along with the magnitude and avidity of the antibody response when present.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that have proposed transmission of wild-type virus followed by selection of resistant variants that were only detectable by sensitive assays based their interpretation on the timing of infection and likely exposure to NVP [10,11,23]. A similar interpretation should follow when population sequencing shows mixed wild-type and resistant viruses, unless both forms were simultaneously transmitted; a scenario less likely given the genetic bottleneck of MTCT of HIV [24,25] and the fact that most (~80%) HIV infections in heterosexuals [18,26] and infants via breast milk [27] result from transmission of a single virus. Thus, our study is important in that it establishes the NVP-R breast milk virus population selected by maternal sdNVP as the origin of the NVP-R virus in this postnatally-infected infant.…”
Section: Resultsmentioning
confidence: 99%